2020
DOI: 10.17759/cpse.2020090308
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of Transcranial Direct Current Stimulation as an Augmentation Strategy for Attention Bias Modification Treatment in Adolescents with Anxiety Disorders

Abstract: This article presents the results of a case series to assess the feasibility, acceptability, and clinical promise of transcranial Direct Current Stimulation (tDCS) as an augmentation strategy in clinic referred adolescents. Attention Bias Modification Treatment (ABMT) is a computer-based attention-training protocol designed to reduce rapidly deployed attention orienting to threat and thereby reduce anxiety symptom severity. Studies of ABMT reveal overall small to medium effect sizes. Advances in the neural und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…We identified 33 eligible studies (total N = 517; age range 2-25 years, M = 15.53, SD = 6.44; 82.2% male), composed of eight double-blind RCTs [37-40, 43, 44, 46, 48], four double-blind, crossover RCTs [35,43,45,47], one doubleblind, sham-controlled trial [67], two single-blind RCTs [41,63], one single-blind controlled clinical trial [65], four openlabel studies [36,38,44,62], and 14 case series/studies [42, 51-61, 64, 66] (see Table 1 and 2). Seven studies were in ASD [35][36][37][38][39][40][41][42][43], seven in ADHD [44][45][46][47][48][49][50], four in schizophrenia [51][52][53][54], two in OCD [55,56], Tourette's syndrome [57,58], depression [59,60], anxiety [61,62], or substance abuse disorder [63,64], and one each in eating disorders…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 33 eligible studies (total N = 517; age range 2-25 years, M = 15.53, SD = 6.44; 82.2% male), composed of eight double-blind RCTs [37-40, 43, 44, 46, 48], four double-blind, crossover RCTs [35,43,45,47], one doubleblind, sham-controlled trial [67], two single-blind RCTs [41,63], one single-blind controlled clinical trial [65], four openlabel studies [36,38,44,62], and 14 case series/studies [42, 51-61, 64, 66] (see Table 1 and 2). Seven studies were in ASD [35][36][37][38][39][40][41][42][43], seven in ADHD [44][45][46][47][48][49][50], four in schizophrenia [51][52][53][54], two in OCD [55,56], Tourette's syndrome [57,58], depression [59,60], anxiety [61,62], or substance abuse disorder [63,64], and one each in eating disorders…”
Section: Resultsmentioning
confidence: 99%
“…A single-arm, open-label study [62] in six adolescents with social anxiety disorder or generalized anxiety disorder reported that combined anodal-tDCS to the left-DLPFC with attention bias modification training reduced self-and parent-reported total anxiety symptoms, self-and parentrated anxiety-related emotional symptoms, and clinicianrated anxiety symptoms, compared to baseline. However, only self-reported total anxiety symptoms significantly reduced from baseline to post-stimulation [62].…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…five in ADHD [35][36][37][38][39], four in schizophrenia [40][41][42][43], two each in OCD [44,45], Tourette's syndrome [46,47], depression [48,49], anxiety [50,51], or substance abuse disorder [52,53], and one each in eating disorders [54], catatonia [55], or co-comorbid ASD, ADHD and anxiety [56]. Across studies, tDCS was typically delivered for 20 to 30-mins (M=23; SD = 4.43) once-daily over 4 to 28 sessions (M=12; SD = 7.07).…”
Section: Resultsmentioning
confidence: 99%
“…1), composed of six double-blind RCTs, one double-blind, sham-controlled trial, two single-blind RCTs, one single-blind controlled clinical trial, four open-label studies, and 14 case series/studies (see Table 1 and 2). Six studies were in ASD [29-34], five in ADHD [35-39], four in schizophrenia [40-43], two each in OCD [44,45], Tourette’s syndrome [46,47], depression [48,49], anxiety [50,51], or substance abuse disorder [52,53], and one each in eating disorders [54], catatonia [55], or co-comorbid ASD, ADHD and anxiety [56]. Across studies, tDCS was typically delivered for 20 to 30-mins (M=23; SD = 4.43) once-daily over 4 to 28 sessions (M=12; SD = 7.07).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation